RECOVERY ENZIM PROTEASE DARI JEROAN IKAN TUNA DENGAN TEKNOLOGI ULTRAFILTRASI DAN REVERSE OSMOSIS - Bambang Riyanto; Uju .; Sofia Halimi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
Tuna viscera is highly potential as a source of protease enzyme. A wide enzyme applications requires an economical and efficient enzyme purification techniques and therefore can be applied in a large scale. The ultrafiltration (UF) process is one of the potential technology but has disadvantage due to fouling and concentration polarization. The studies on the operating trans-membrane pressure (TMP), the operating temperature, materials of the membrane and the molecular weight cut off (MWCO) of the membrane to reduce fouling and concentration polarization should be carried out. Reverse osmosis (RO) process at the next step was used to increase the concentration of the protease enzyme. This study was divided into several stages of preparation of protease enzyme, crude extract, pre-filtration, UF process, RO process and SDS-PAGE analysis. The tests included measurements of protein levels and activity of the protease enzyme. Optimum conditions for the purification of the UF polyacrylonitrile with MWCO 100 kDa was obtain on TMP 55 kPa and a temperature of 40 °C. Flux in both membrane was influenced by the TMP, temperature, the membrane material and MWCO. Rejection of protein and enzyme activity in both membrane is more influenced by the membrane material and MWCO of the membrane. Estimation of protein molecular weight after the RO from UF polyacrylonitrile with MWCO 100 kDa were 37.53; 27.77; 22.72 and 19.88 kDa while the specific activity of the protease was 1.38 unit/ mg.Keywords: protease, tuna viscera, ultrafiltration, reverse osmosis.